The Seven Oaks Incident and the Construction of a Historical Tradition, 1816 to 1970 - Dick, Lyle (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
AbstractThe Seven Oaks incident, a violent clash between Métis and Hudson's Bay Company/Selkirk settlers at Red River in 1816, was long represented in Canadian historical discourse as a "massacre." In investigating the genesis of this interpretation, the paper examines the primary record and employs textual analysis to distinguish the "story," or basic facts, from the "discourse," or rhetorical overwriting by the event's historians. The paper also reexamines the respective roles of amateur and professional historians in Western Canadian historiography in the context of the discourse on Seven Oaks. The contemporary report of Commissioner William Coltman and works of Red River amateurs are used to establish that Seven Oaks was generally not considered a "massacre" inthepre-Confederationera. Rather, this interpretation largely dates from the post-1870 period, when Anglo-Canadian immigrants to Western Canada became the region's ruling group. Anglo-Canadian historians utilised partisan accounts of the battle and romantic plot structures to reinterpret the Métis actions as a savage slaughter. In these narratives, the alleged Métis role at Seven Oaks functioned allegorically to justify the dispossession of this western Native group's lands by the newcomers. In structuring their texts to promote the ideological position of their own ethnic group, post-Confederation academics established a tradition of writing that dominated Seven Oaks historiography for one hundred years. Since 1970, this tradition has weakened somewhat in academic circles, while popular historians have continued to reproduce its essentials in their accounts.